USE OF THE E-VOTING SYSTEM TO MAKE IT HAPPEN DEMOCRATIC ELECTIONS - Fawwaz Iqbal Rahmanto; Syofyan Hadi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Democratic elections are an essential element in a sovereign government system, where the voting rights of every individual are valued, and the selection process is conducted in a fair, transparent, and efficient manner. To enhance the quality and efficiency of elections, e-voting technology has been introduced as an alternative to traditional voting methods. This study discusses the use of e-voting systems to achieve more democratic elections, focusing on aspects of security, transparency, accessibility, and efficiency. The results of the study show that e-voting has significant potential to increase voter participation, reduce operational costs, and expedite the vote-counting process. However, challenges related to data security, system integrity, and resistance to technological change must be addressed to ensure successful implementation. Overcoming these challenges requires robust cybersecurity measures, rigorous testing, and comprehensive voter education. With proper oversight and careful adoption of technology, e-voting can become an effective solution to support a more democratic process. Additionally, collaboration between government bodies, technology providers, and civil society is crucial to build trust and ensure the system's credibility. This study concludes that while e-voting offers numerous advantages, it is imperative to implement comprehensive measures to mitigate risks and maintain the integrity of the electoral process, ultimately fostering a more inclusive and participatory democracy.